Effect of crystallographic structure of iridium based oxides on electrochemical degradation. (10th January 2018) - Sun, Wei; Cao, Li-Mei; Yang, Ji
Abstract: Developing new anode materials is an effective strategy to overcome the growing challenges in electrochemical treatments. Material crystal structure is a critical factor in governing catalytic activity, but is often neglected in designing degradation electrodes. Here, we investigate the role of crystal structure using six different Ir-oxides with three different crystal structures in electrochemical degradation. Hollandite structure (Kx IrO2 and K1.6 (Mn0.78 Ir0.22 )8 O16 ) with 2 × 2 tunnel size obtains higher removal performance than that of other structure oxides, such as packed pyrochlore (Pb2 Ir2 O6.5 and Bi2 Ir2 O7 ) and rutile (IrO2 and Cu0.3 Ir0.7 Oσ ). Catalysts with same crystal structure show similar morphology features and have almost same degradation performance, although their electrochemical properties are quite different. The presence of tunnel structure in oxides may be responsible for excellent degradation performance of corresponding catalysts. Additionally, tunnel structure oxides with good oxygen evolution reaction (OER) activity can reduce the energy consumption due to low cell potential. Our findings bring an opportunity for developing new catalysts for electrochemical treatment technologies. Highlights: SP electrochemical degradation performance depends on material crystal structure. Hollandite structure exhibits better performance than rutile and pyrochlore structure. An appropriate OER activity is beneficial to lowering cell potential.